(untitled) (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2026)
The “Rimba dan Budaya” destination in West Kalimantan possesses considerable natural and cultural tourism potential, yet its contribution to regional economic development remains limited, as reflected by low international tourist arrivals and the tourism sector’s 2.09% share of the provincial Gross Regional Domestic Product (GRDP). This study examines the implementation of destination management, identifies its key determinants, and proposes strategic recommendations to strengthen destination governance. An exploratory qualitative case study was employed using observations, document analysis, semi-structured interviews with six key informants, and a SWOT questionnaire involving 40 stakeholders from government, community, and private sectors. The findings reveal challenges in market-oriented planning, institutional coordination, human resource capacity, and destination branding. Five key determinants were identified, with stakeholder commitment, particularly from local communities, emerging as the most influential. SWOT analysis places West Kalimantan in the Strength–Opportunity (SO) quadrant, indicating a growth-oriented strategy. This study contributes a public administration-based destination management model integrating institutional capacity, stakeholder commitment, and collaborative governance to support sustainable tourism development.